Kajian Geologi Blok “X” Pani Gold Project, Kecamatan Buntulia, Provinsi Gorontalo - Siti Humaira Panigoro; Yayu Indriati Arifin; Ayub Pratama Aris (Universitas Negeri Gorontalo, 2026)
This study was conducted in Block “X” of the Pani Gold Project Area, Buntulia District, Pohuwato Regency, Gorontalo Province, with the aim of examining the regional geological conditions, including geomorphology, stratigraphy, and geological structures. The methods applied consist of geological field mapping supported by petrographic analysis. The results indicate that the study area is divided into two main geomorphological units, namely a volcanic hill unit that dominates the area with undulating to steep morphology, and an alluvial plain unit developed along river systems. The stratigraphy of the study area comprises four lithological units, including granodiorite, diorite porphyry, dacite porphyry of Pliocene age, and alluvial deposits of Holocene age. The geological structures identified include fracture systems and normal faults with a sinistral (left-lateral) component trending northeast–southwest, as well as the presence of fault gouge and fault breccia indicating relatively intense deformation. Overall, the geological characteristics of the study area reflect a strong relationship between lithology, geomorphology, and structural controls in shaping the landscape development.